The pinprick approach: Whitehall’s top-secret anti-communist committee and the evolution of British covert action strategy - Cormac, Rory (MIT Press, 2014)
This article examines Great Britain’s approach to covert action during the formative years of British Cold War intelligence operations, 1950–1951. Rather than shy away from such activity in the wake of the failure in Albania in the late 1940s, the British increased the number of operations they pursued. This was the start of a coherent strategy regarding covert activity that can be conceptualized as the “pinprick” approach. The strategy was overseen by a highly secretive Whitehall body, the Official Committee on Communism, which in effect became the government’s covert action committee. This article uses the commission’s recently declassified papers for the first time to assess the merits of this approach.